Legal dualism of priority rights for tax debts by the state when taxpayers go bankrupt - Putri, Zahra Malinda; Sinaga, Mhd Panca Prana Mustaqim; Mbunai, La Ode (Privietlab, 2025)
The existence of dual regulations governing the State's preferential right to tax debt repayment presents a distinct issue in resolving matters related to taxpayers who have been declared bankrupt by the court. The two domains of public law and civil law both regulate the privilege of priority in the repayment of debts by the debtor. Therefore, an in-depth analysis is necessary to address the issue of tax debt repayment when a taxpayer has been declared bankrupt. The objective of this study is to analyze and seek answers regarding the position of the state as a creditor in the repayment of tax debts, as well as to provide an analysis of the regulation concerning the State’s preferential right over tax debts. The research method used is a qualitative normative approach, utilizing secondary data and descriptive-analytical techniques for data analysis. The results of this study indicate that the state holds a higher position than other types of creditors as regulated in the Bankruptcy and Suspension of Debt Payment Obligations Law (BSDPO Law), and therefore must be given priority. However, the two sets of regulations remain unreconciled in terms of harmonizing the position of creditors in fulfilling tax debt obligations. Moreover, the regulation regarding the repayment of tax debts mandates that such debts must be settled before the repayment of other types of debts owed by the debtor.